LEGAL ACCOUNTABILITY AND INTEGRATION OF SHARIA PRINCIPLES IN THE MANAGEMENT OF VILLAGE-OWNED ENTERPRISES (BUMDES) IN INDONESIA - Alam, Faris Satria; Rohman, Mohamad Mujibur; Putra, Gilang Rizki Aji (IBN KHALDUN BOGOR, 2024)
Management of Village-Owned Enterprises (BUMDesa) in Indonesia has become the focus of attention in improving public service quality and community welfare. In this context, the integration of sharia principles in the management of BUMDesa becomes very important to ensure compliance with religious and ethical values. This article discusses the importance of legal accountability and integration of sharia principles in the management of BUMDesa in Indonesia. Using library research methods, this article finds that the integration of sharia principles in the management of BUMDesa can increase legal accountability and transparency in financial management. In addition, this article also shows that the integration of sharia principles can ensure compliance with religious and ethical values in the management of BUMDesa. The results of this research can be a reference for the government and BUMDesa managers in improving the quality of BUMDesa management and improving community welfare.